Revision of the family Nothybidae (Diptera: Schizophora) - Lonsdale, O.; Marshall, S.a. (Zootaxa, 2016)
The family Nothybidae (Diptera: Schizophora) is revised. The family consists of 11 species in the single genus Nothybus Rondani, which occurs in Papua New Guinea, Nepal and much of the Oriental Region. Three species are described as new: N. absens spec. nov. (China), N. cataractus spec. nov. (Laos, Thailand) and N. procerus spec. nov. (India). Nothybus longithorax Rondani, 1875 is treated as a junior synonym of N. longicollis (Walker, 1856). Nothybus decorus Meijere, 1924 syn. nov. is included as a junior synonym of N. lineifer Enderlein, 1922.